A comprehensive organisational model for the effective management of project management - C. J. Brown (South African Journal of Business Management, 2008)
This paper is not primarily aimed at project leaders, but at the decision-makers on project management in organisations. The purpose is to expose the not-so-obvious organisational complications which confront project managers in the management of projects. The point of departure is to establish a comprehensive approach to creating an organisational environment conducive to project management excellence in an organisation.In the arenas of business and management, the principles of project management is relatively simple and much of it actually common sense. However, it is the experience of many project leaders that the mere application of appropriate project management processes and techniques, by no means guarantee that the management of projects will be effective on a continuous basis. On investigation of that premise, this paper reports on research that identified organisational variables that can affect the organisational strategy, structure, culture, systems, behavioural patterns and processes of an organisation, which comprehensively determine the internal environment pre requisites for project management to be exercised successfully.The rationale of the paper is to re-emphasise, but also to investigate progress on the stern warning by Nicholas (1990:481) nearly two decades ago that organisations should not jump into project management precipitously, but with a well-developed and organisation-fitted strategy and game plan.
Keywords: 650